Analysis of The Interaction of Monetary Policy and Islamic Investment Towards Indonesia's Economic Growth - Yusuf, Mohammad; Asmuni, Asmuni; Harahap, Isnaini (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Economic growth is the main measure of development success, and the results of economic growth will be enjoyed by the community either by itself or with government intervention. Economic growth is an important indicator in the real sector. The interaction between monetary policy and sharia investment in influencing Indonesia's economic growth is the main focus of this study. This study aims to analyze the effect of the interaction of monetary policy (interest rates, exchange rates and money supply) and the interaction of sharia investment (sukuk, sharia stocks, sharia mutual funds) on Indonesia's economic growth for the period 2000-2022. This type of research is quantitative research using time series data from secondary data with the Vector Error Correction Model (VECM) analysis method with the help of Eviews software. The results of this study indicate that the variables of short-term interest rates, SUKUK, sharia stocks, sharia mutual funds have a positive and significant effect on economic growth, while the rupiah exchange rate (KURS), the amount of money in circulation on economic growth show a negative and insignificant effect. The variables of long-term interest rates, rupiah exchange rates or KURS, the amount of money in circulation SUKUK, sharia stocks, mutual funds have a positive and significant effect on economic growth